Effects of age and sex on eye movement characteristics - Junichi Takahashi; Kenichiro Miura; Kentaro Morita; Michiko Fujimoto; Seiko Miyata; Kosuke Okazaki; Junya Matsumoto; Naomi Hasegawa; Yoji Hirano; Hidenaga Yamamori; Yuka Yasuda; Manabu Makinodan; et al. (Wiley, 2021)
Abstract Abnormal eye movements are often associated with psychiatric disorders. Eye movements are sensorimotor functions of the brain, and aging and sex would affect their characteristics. A precise understanding of normal eye movements is required to distinguish disease‐related abnormalities from natural differences associated with aging or sex. To date, there is no multicohort study examining age‐related dependency and sex effects of eye movements in healthy, normal individuals using large samples to ensure the robustness and reproducibility of the results. In this study, we aimed to provide findings showing the impact of age and sex on eye movement measures. The present study used eye movement measures of more than seven hundred healthy individuals from three large independent cohorts. We herein evaluated eye movement measures quantified by using a set of standard eye movement tests that have been utilized for the examination of patients with schizophrenia. We assessed the statistical significance of the effects of age and sex and its reproducibility across cohorts. We found that 4‐18 out of 35 eye movement measures were significantly correlated with age, depending on the cohort, and that 10 of those, which are related to the fixation and motor control of smooth pursuit and saccades, showed high reproducibility. On the other hand, the effects of sex, if any, were less reproducible. The present results suggest that we should take age into account when we evaluate abnormalities in eye movements.